MO115: Cardiorenal Units as Management Strategy to Improve Outcomes in Cardiorenal Syndrome. (3rd May 2022) - Marques, Maria; Cobo, Marta; García Magallón, Belen; Luisa Serrano Salazar, Maria; Vazquez Lopez-Ibor, Jorge; Lopez, Paula; Janeiro, Dario; Portoles, Jose M
Abstract: BACKGROUND AND AIMS: Cardiorenal syndrome (CRS), defined as the spectrum of disorders that acutely or chronically affect both heart and kidney function, is often a challenging condition with paucity of evidence-based therapy. The increasing burden of this entity has prompted the creation of cardiorenal units (CRU) as integrating programs intended to provide a combined multidisciplinary approach to maximize all chances for organ and patient recovery. Here we describe the early results of the creation of one CRU in a high complexity university hospital. METHOD: This observational study included all patients diagnosed with CRS, who have been seen in the cardiorenal day care unit, formed by specific trained nephrologist, cardiologist and nurses. Assessment of cardiorenal function and volume status was performed by conventional cardiac ultrasound plus V-Scan, GFR estimation by CKD EPI, NT-proBNP determination and bioelectrical impedance when indicated. RESULTS: Cardiorenal Unit of Puerta de Hierro University Hospital was created in January 2021. A total of 68 patients have been evaluated with a mean follow-up of 4 months (SD 3.2). Most frequent cardiologic diagnoses were 63.9% heart fellow with reduced function (HFrF) and 37.1% heart failure with preserved ejection fraction (HFpEF) and the presence on pulmonary hypertension or tricuspid regurgitation were 29.4% and 50.9%. 51.6% patients showed diuretic resistance. Most frequent renal diagnosis were pure CRS 36.9%, and 27.7% and 24.6% CRS associated to diabetic kidney disease or nephroangioesclerosis, respectively. Mean FGe rate when patients were initially evaluated was 31.5 mL/min/1.73 m 2 (SD 11.0) with demonstration of albuminuria in 48.5% of patients. The integrated cardiorenal management of these patients included initiation or adjustment of specific cardio-nephroprotective drugs [SGLT2 inhibitors (46.8%), ARNi (25.8%), aldosterone receptor antagonists (4.8%)] or diuretic regime adjustment including iv administration (54.8%). Peritoneal dialysis was indicated in three patients and haemodialysis in one patient. Approximately 13.2% patients suffer new episodes of heart failure that needed hospitalization or unexpected medical attention at the day-care clinic. One patient died during follow-up (1.5%). CONCLUSION: We conclude that this coordinated cardionephro approach of CRS was useful to optimize drug therapy aimed to mid-long term goals of cardionephro protection and to implement advanced therapies for fluid management in patients with diuretic resistance.